APLIKASI KESEHATAN IBU ANAK (KIA) DALAM MEMANTAU PERKEMBANGAN BAYI MELALUI DETEKSI DINI TUMBUH KEMBANG (DDTK) BAYI DAN SISTEM POSYANDU - Hariyono Rakhmad; Nugroho Setyo Wibowo (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
Posyandu includes recording a baby's development and do still use the manuals that guide maternal and child health (KIA handbook) in general. Implementation and use of books Maternal and Child Health (KIA handbook) is only a small part of information obtained for both health care workers and users. This problem is the recording of the baby's condition is not good and is not documented. So the solution is carried out in activity is to design and create a Computer Application Monitoring Maternal and Child Health is devoted to data processing for KIA. Several stages in the implementation is (1) Analysis and Identification System, (2) Literature, (3) Program Design (4) Implementation/Programming, (5) Preparation Module, and (5) Evaluation and reporting. In the final stage of this activity is to operate a computer training program KIA, with modules that have been provided. However, due to the limited capabilities of each cadre Posyandu, it still requires continual assistance